Pruning of orchard trees - Nichols, Roscoe Townley (My University, 1899)
Introduction: The Subject of pruning is of the utmost importance to the horticulturist. Upon the thoro understanding of its principles and methods depends the success of the orchard. Scientific pruning of the fruit tree at different stages of its growth, is absolutely necessary in order to obtain the best results. It so happens that the stem or subject is in a transitional stage at the present time, so that no absolute rules can be laid down for the amateur fruit-grower. A thoro understanding of the principles should be obtained before you start to prune. And then, keeping these principles always in view the operation should be varied to suit the conditions and environment of the individual plant under consideration. What would be the proper treatment to give the desired result under one set of conditions, might produce just the opposite results under a different set. The transitional period is due, to some extent to the attempted introduction of entirely new methods by Mr. H. M. Stringfellow, of Galveston, Texas. He has proposed a system of pruning, which, if adopted, would entirely change the methods and principles which govern orchard setting at the present time.
Citation: Nichols, Roscoe Townley. Pruning of orchard trees. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Accepted Methods of Pruning; New Methods of Pruning; Pruning to Increase Vigor; Theses; Manuscripts (documents)